Hermeneutika Derrida Vis A Vis Formulasi Pemikiran Imam al-Sha'rani dalam Kitab al-Mizan al-Kubra - Ahmad Faizal Basri, Fais; Mustaqim (Mahad Aly Al Fithrah Press, 2020)
Al-Sha’ra>ni> was a shufi figure who was able to give innovations in the face khilafiah al-'Ummah. This figure is very meritorious with his opus entitled al-Miza>n al-Kubra>. Because accommodated all of opinions Ulama’ without exception, as long does not contradict with nash of the Qur'an and hadith. The aggregation of all opinions by al-Sha’ra>ni> it is the only 'ala> sabi>l al-Ta'zi>m; On the basis of respecting the hard work of Ulama’. As for this kind of attitude, it is almost similar with Derrida's thought with his theory of deconstruction. This study aims to compare derrida's hermeneutics vis a vis with the formulation of Al-Sha’ra>ni> thought in his opus. This research uses this type of literature research. Then, the collected data is analyzed by inductive and comparative methods. The result of this study is that the two figures are equally accommodating all opinions, without siding with one opinion alone and marginalizing other opinions. The second equation is derrida’s opinion